The Implementation of Google Classroom for Eight Grade Students at SMP Ayodhya Pura Selat - Arta, Kadek Agus Redi; Juniarta, Putu Krisna Adi; Dewi, Kadek Sintya (English Education Department STKIP Agama Hindu Singaraja, 2022)
Education is a critical aspect in the advancement of a country. They received the new thing through adequate education which they can use to generate superior human resources. Based on this age, new technologies are being developed to make the education in learning process easier. One of the examples of an online learning platform is Google Classroom. The purpose of this research is to identify the implementation of Google Classroom and what problem are faced by students on the use of Google Classroom in online English learning. The method of this study is qualitative research to collect the data. The data is collected by using observation to the middle school at SMP Ayodhya Pura Selat and interview guide to the 8 grade students. The result shows students feel Google Classroom is ineffective used in learning process cause of some problems such as the internet connection, the task implementation in Google Classroom felt difficult than face to face in the school, limitation in supporting equipment such as smartphone and laptop to conduct the online learning.